MEDIASI MEDIASI SEBAGAI ALTERNATIVE DISPUTE RESOLUTION (ADR) DALAM KASUS PAKET HILANG / RUSAK PADA EKSPEDISI SHOPEE EXPRESS PAMEKASAN HUB - Firmansyah, Hendri; Hariyanto, Erie; Fadllan (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the issue of Mediation as an Alternative Dispute Resolution (ADR) in Cases of Lost/Damaged Packages in Shopee Express Pamekasan Hub. Consumer disputes in expedition services are a crucial issue, given that business actors are fully responsible for losses suffered by consumers. This study applies a normative legal method that focuses on the analysis of legal norms, principles, doctrines, and applicable laws and regulations. This study uses a descriptive qualitative approach with a case study method. As a solution, this dispute is resolved through mediation. The mediation process usually occurs if internal resolution through the return feature or direct contact with customer service fails or is rejected by one of the parties. This process involves a third-party mediator who is tasked with bridging communication between consumers and Shopee Express representatives to reach a peaceful and fair mutual agreement.